2018
DOI: 10.1007/s00467-017-3868-0
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination titres pre- and post-transplant in paediatric renal transplant recipients and the impact of immunosuppressive therapy

Abstract: These data show a low percentage of patients with positive vaccination titres pre-transplant, a low revaccination rate post-transplant with limited antibody response, and a high rate of vaccination titre losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Similar to our study, the younger patients in this prior cohort tended to have higher rates of undetectable titers raising concern over lack of sustained response to childhood vaccine series in those with concomitant illnesses or perhaps differences in age‐related vaccines practices or exposures. Furthermore, Hocker et al studied 155 pediatric renal transplant candidates and found that before transplantation, only 77.4% of patients had a positive measles titer, despite a complete vaccination schedule, compared to healthy children at 97% 5 . The same trends were found when the group studied mumps, rubella, and varicella titers in these children.…”
Section: Discussionmentioning
confidence: 83%
“…Similar to our study, the younger patients in this prior cohort tended to have higher rates of undetectable titers raising concern over lack of sustained response to childhood vaccine series in those with concomitant illnesses or perhaps differences in age‐related vaccines practices or exposures. Furthermore, Hocker et al studied 155 pediatric renal transplant candidates and found that before transplantation, only 77.4% of patients had a positive measles titer, despite a complete vaccination schedule, compared to healthy children at 97% 5 . The same trends were found when the group studied mumps, rubella, and varicella titers in these children.…”
Section: Discussionmentioning
confidence: 83%
“…28 These findings are consistent with the observations that rituximab eliminates peripheral B cell memory in a dose-dependent manner, 29 a depletion that may be prolonged. 30 Importantly however, 5 of 8 participants (63%), of whom 4 were not receiving immunosuppression, developed anti-HPV responses to vaccination despite rituximab exposure at least 6 months previously; other reports suggest that such patients may develop a vaccine response. 31 The HPV vaccination schedules used after allogeneic hematopoietic cell transplant were recommended by expert transplant and infectious disease committees following populationbased age recommendations.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in another study, investigators revealed that the re-vaccination during the posttransplant period showed titer loss or failed to induce positive IgG for diphtheria, pertussis and hepatitis B in nearly 40% of their patients [22]. However, there are some controversial studies in the literature.…”
Section: Discussionmentioning
confidence: 97%